ANALYSIS OF WORKING CAPITAL FINANCING MEMBER OF REVENUES IN CONVENTIONAL AND ISLAMIC COOPERATION - Dian Lestari; Saparuddin Mukhtar; Herlitah Herlitah (Jurnal Ilmiah Econosains, 2017)
This study aims to determine the effect of working capital financing on revenues of members businesses at PEMK Cengkareng Timur Cooperative and BMT Ta'awun Finance, the difference of revenues of members businesses after and before receiving working capital financing from PEMK Cengkareng Timur Cooperative and BMT Ta'awun Finance, and difference revenues of members businesses after receiving working capital financing between Koperasi PEMK Cengkareng Timur and BMT Ta'awun Finace. Methods of data acquisition used with structured interview methods and in-depth interviews. The population in the study were all members who received working capital financing in 2016 at PEMK Cengkareng Timur Cooperative and BMT Ta'awun Finace. The sample used is 30 members from each cooperative with sampling technique in the form of census and purposive sampling. Data analysis used is multiple regression analysis, paired t sample test, and independent t test sample test. The result of research is showed there is the effect of working capital finance with revenues of members businesses at PEMK Cengkareng Timur tcount (2,142) > ttable (2.048) and in BMT Ta’awun Finance tcount (2,688) > ttable (2.048), there is difference before and after working capital financing to revenues of members businesses in both cooperatives because of the probability value of 0,000 <0.05, and there is a difference in the income of members who receive working capital financing from the two cooperatives seen from tcount 0.00 <0.05.